1994
DOI: 10.1002/macp.1994.021950606
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterizations of copolymer films with pendant monosaccharides

Abstract: We copolymerized a monomer with a pendant glucose unit (GEMA) with methyl methacrylate (MMA) and prepared copolymer films with pendant monosaccharides by casting the copolymer solution on glass plates. The surfaces of the copolymer films were characterized by contact angle measurements, X-ray photoelectron spectroscopy (XPS) and protein adsorption measurements, and compared with the surface of 2-hydroxyethyl methacrylate (HEMA)-MMA copolymer films. The surface free energy of the GEMA-MMA and HEMA-MMA copolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…X-ray photoelectron spectroscopy (XPS) has long been used for characterizing polymer surfaces and the modification of polymer surfaces, such as new chemical structures introduced by plasma 21) , UV 12) , additives 22) , and surface grafting 23) . Polymers having pendant saccharides were investigated by Nakamae et al using XPS recently 14,15) . In a previous paper the surfaces of styrene/3 copolymers were well characterized by angular dependent XPS and contact angle measurement 16) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray photoelectron spectroscopy (XPS) has long been used for characterizing polymer surfaces and the modification of polymer surfaces, such as new chemical structures introduced by plasma 21) , UV 12) , additives 22) , and surface grafting 23) . Polymers having pendant saccharides were investigated by Nakamae et al using XPS recently 14,15) . In a previous paper the surfaces of styrene/3 copolymers were well characterized by angular dependent XPS and contact angle measurement 16) .…”
Section: Resultsmentioning
confidence: 99%
“…Saccharides may impart more functions and hydrophilicity to commercial polymers, therefore, to amend their antistatic property, dyeability, adhesion, printability, and biocompatibility. Nakamae et al copolymerized 2-(glycosyloxy)ethyl methacrylate with methyl methacrylate or styrene, and investigated the surface properties and protein adsorption of the copolymer films 14,15) . Wulff et al investigated the surface characteristics of copolymers of styrene and 2,3;4,5-di-O-isoprop-ylidene-1-(4-vinylphenyl)-D-gluco(D-manno)pentitol by contact angle measurement, XPS, and electrical surface resistance measurement 16) .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kitazawa et al 2 reported the direct synthesis of a sugar ester derivative, namely glycosyloxyethyl methacrylate (Fig 1, 1 ) by reaction between O ‐methylglucopyranoside and hydroxyethylmethacrylate in the presence of an acidic catalyst. Copolymerization of this monomer with methyl methacrylate was found to be ideal, as evidenced by quite similar reactivity ratios 3. The derivatization of disaccharides such as sucrose to yield monomethacryloylsucrose ester (Fig 1, 2 ) was also described in a one‐pot synthesis in aqueous medium 4…”
Section: Introductionmentioning
confidence: 89%
“…52 We synthesized a variety of carbohydrate polymers by copolymerizing a monomer with pendant glucose (2-glucosyloxyethyl methacrylate: GEMA) and hydrophilic or hydrophobic monomers and examined their unique surface properties under various conditions. [53][54][55][56][57][58] Furthermore, complex formation between Con.A and polymers with pendant glucose (PGEMA) was investigated to design a glucose-responsive polymer. 59 When Con.A was added to a buffer solution containing PGEMA, the solution became turbid due to multiple associations between PGEMA and Con.A.…”
Section: Glucose-responsive Hydrogelsmentioning
confidence: 99%